1993
DOI: 10.1038/ki.1993.189
|View full text |Cite
|
Sign up to set email alerts
|

Viral DNA in microdissected renal biopsy tissue from HIV infected patients with nephrotic syndrome

Abstract: Focal glomerulosclerosis (FGS) has been considered as HIV-associated nephropathy, a specific renal complication of infection. To determine whether renal disease in HIV infected patients has one highly prevalent pathologic expression, and whether renal parenchymal viral genomic incorporation affects pathologic outcome, we reviewed renal biopsies performed at our center. Twenty-eight HIV infected patients with nephrotic range proteinuria underwent renal biopsy for diagnosis of renal disease: 85.7% led homosexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(49 citation statements)
references
References 28 publications
1
47
0
1
Order By: Relevance
“…Cohen et al (1) first reported the presence of HIV RNA in podocytes as revealed by in situ hybridization (ISH) in 1989, a finding that was supported by microdissection studies of Kimmel et al (2). These studies were difficult to validate because of the failure of others to replicate these findings using conventional techniques of ISH, the inability to demonstrate the presence of viral peptides in renal parenchymal cells by immunohistochemistry, and the inability to demonstrate appropriate receptors for viral entry into cells, namely CD4 and the chemokine receptors CXCR4 or CCR5, on renal parenchymal cells (3).…”
Section: Hiv-associated Nephropathymentioning
confidence: 64%
“…Cohen et al (1) first reported the presence of HIV RNA in podocytes as revealed by in situ hybridization (ISH) in 1989, a finding that was supported by microdissection studies of Kimmel et al (2). These studies were difficult to validate because of the failure of others to replicate these findings using conventional techniques of ISH, the inability to demonstrate the presence of viral peptides in renal parenchymal cells by immunohistochemistry, and the inability to demonstrate appropriate receptors for viral entry into cells, namely CD4 and the chemokine receptors CXCR4 or CCR5, on renal parenchymal cells (3).…”
Section: Hiv-associated Nephropathymentioning
confidence: 64%
“…Acute renal failure secondary to tubular injury is also frequent in AIDS (6). In cases of HIVAN, viral antigens and genome have been demonstrated in microdissected renal tissues (8), but the permissiveness of renal cells to replication of HIV-1 is still controversial (9)(10)(11)(12)(13)(14). The finding of apoptotic cells in glomeruli and especially in tubuli of HIV patients may suggest a possible mechanism of HIV-induced renal damage (15).…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, it is characterized by the development of proteinuria usually followed by rapid progression to renal failure; pathological features include focal and segmental glomerulosclerosis with characteristic glomerular collapse, podocyte hyperplasia, pronounced tubulo-interstitial inflammation and microcystic tubular dilation, and epithelial dedifferentiation, proliferation, and apoptosis (6)(7)(8)(9). HIVAN results from direct epithelial infection (10)(11)(12)(13); however, the mechanisms underlying disease susceptibility and progression remain unknown.…”
mentioning
confidence: 99%